Onomastic analysis of cats’ given names - Jaber, Maisa S. (Onomázein, 2024)
This study was designed to investigate cats’ given names in an Arabic-speaking community of Jordan. For the purpose of this study, a questionnaire was prepared and distributed or displayed on the Facebook page Ask Jordan. A number of 153 names were collected, studies analyzed and then categorized. The results reveal that, in Jordan, the names of cats fall into different categories classified in accordance with the cat’s physical appearance, a cartoon or a movie character, the cat’s gender, a classic name, a new name, and a circumstantial name. The results also reveal a difference between names of stray cats and purebred house cats. The study ends with a recommendation for further studies to analyze names of pet cats in other countries.